Intensity dependence of the dissociative ionization of DCl in few-cycle laser fields. (24th November 2015) - Li, H; Tong, X M; Schirmel, N; Urbasch, G; Betsch, K J; Zherebtsov, S; Süßmann, F; Kessel, A; Trushin, S A; Paulus, G G; Weitzel, K-M; Kling, M F
Abstract: We have studied the dissociative ionization of DCl in 4 fs laser fields at 720 nm central wavelength using intensities in the range (1.3–3.1) × 10 14 W cm −2 . By employing the phase-tagged velocity-map imaging technique, information about the angular distribution of deuterium ions as a function of their kinetic energy and the carrier-envelope phase is obtained. On the basis of the experimental data and semi-classical simulations, three regions are distinguished for the resulting D + ions with different kinetic energies. The one with the lowest kinetic energy, around 5–7 eV, is from dissociation involving the X-state of DCl +, populated through direct ionization with the laser field. The second region, around 7–11 eV, originates from rescattering induced dissociative ionization. Above 2 × 10 14 W cm −2 D + ions with kinetic energies exceeding 15 eV are obtained, which we ascribe to double ionization induced by rescattered electrons.